The Role and Form of Forestry Police Supervision in Forest Protection and Security in the Sinjai Regency Forest Area - Asikin, Muchtar; Arif, Muhammad; Kultsum, Ummu; Wahyullah; Kadir, Abd. (Fakultas Kehutanan, Universitas Hasanuddin, 2025)
This study aims to determine and analyze the role of the Forestry Police in protecting and securing forests and the form of supervision of the Forestry Police in protecting and securing forests in the forest area of ​​Sinjai Regency. This research method is a survey method with data collection techniques being observation and distributing questionnaires to respondents. Data on the role and form of supervision of the Forestry Police collected from distributing questionnaires were then processed using the SPSS version 25 application. The results of the study show that the role of the Forestry Police in protecting and securing forest areas, forests, forest products, plants, and wildlife is 92.10% (very important), maintaining the rights of the state, society, individuals over forest products, plants, and wildlife is 92.82% (very important), supervising the circulation of forest products is 92.82% (very important), and preventing and protecting natural resources and their ecosystems is 93.16% (very important). The form of supervision carried out by the Forestry Police in protecting and securing forest areas, forests, forest products, plants, and wild animals is a form of direct supervision of 92.08% (very important) and indirect supervision of 90.01% (very important).